SELF-MANAGEMENT DEVELOPMENT OF CAREER GROUPS IN WANG MAN SUB-DISTRICT, WAT SING DISTRICT, CHAI NAT PROVINCE BASED ON THE CONCEPT OF SELF-RELIANCE FOR SUSTAINABLE DEVELOPMENT - Prasert, Sujinda; Srirongthong, Pongsakorn; Sawangnuwatkul, Naphatpapa; Kasemcheunyot, Kaysorn; Srichaisuwan , Supawadee (Journal of MCU Nakhondhat, 2023)
This participatory action research was conducted with the following objectives: 1) to examine the organization and management forms and activities of the career group; 2) to analyze management potential of the career group; and 3) to improve the management of the career group. The key informants who participated in this study consisted of 10 members of Takam Village career group derived from purposive sampling. Data collection and analysis had been done with focus group, SWOT analysis, AIC and AAR techniques, and content analysis. It could be found in the results that: 1) according to POLC self-management model, it could be observed that the career group appeared to have their goals, methods, and resolution defined. In addition, there was an organization of committee appointment and allocation of tasks according to ability. They were found to employ communication and encouragement of team work spirit, and committed to following up and evaluation of work. 2) Key self-management potential was found to include commitment and unity with good leadership and participatory management. In addition, there broom products were inexpensive and durable. And 3) The development model of career group management could comprise of three major aspects. Factors influencing the development of management included unity, leadership, commitment, participation, learning spirit, and external supports. These resulted in the capacity of self-management, self-reliance, and self-development then led to the expansion in activities including the production of brooms, mushroom plantation, chicken raising, and expansion of marketing channel in the community.